Caracterização da deposição de pó cerâmico supercondutor de SmBa2Cu3O7-O em aço inoxidável lean duplex - Lepich, Rodolpho Santos (2017)
Pre-prepared SmBa2Cu3O7-dpolycrystalline superconducting samples were deposited in lean duplex stainless steel and heat-treated withdifferent oxygen flows: 0.2 cm³/s, 0.5 cm³/s and 0.7 cm³/s. In addition, an attempt to heat treatment under an inert argon gas atmosphere was performed. The samples were labeled asA and B, due to the different synthesis processes to which they were submitted. So, to be deposited in the steel it was necessary to create a pit approximately 5cm long by 2mm wide. Through two different processes, corrosion and milling cutter, gave rise to the central channel. After visual analysis, it was noticed that the milling cutter process obtained higher quality and productivity. The superconducting ceramic powder was deposited on the steel and then the material was brought into the furnace for heat treatment. Afterwards, the samples were characterized by X-ray diffraction (XRD) and scanning electronmicroscopy (SEM), as well as the calculation of the mean size of the junction.From the XRD results, it was found that samples A did not form the desired stoichiometry, whereas samples B did. It was observed that the lower the oxygen flow, the greater themean size of the junctions. Consequently, the magnetic shielding is higher. The smaller sizes offer less resistance to the passage of electric current,therefore, thelower theprobability of forming hot spotsand degrading the grain boundaries.Finally, an ideal route for a creation of this composite was found: B synthesis process and thermal treatment under oxygen flow of 0.5 cm³/s. In this case, the desired stoichiometry with a relevant percentageof the orthorhombic and tetragonal phase was formed, however, none of the materials tested showed superconducting transition above 77K